Proceedings of the 18th ACM Great Lakes Symposium on VLSI 2008
DOI: 10.1145/1366110.1366196
|View full text |Cite
|
Sign up to set email alerts
|

Guided test generation for isolation and detection of embedded trojans in ics

Abstract: Testing the genuineness of a manufactured chip is an important step in an IC product life cycle. This becomes more prominent with the outsourcing of the manufacturing process, since the manufacturer may tamper the internal circuit behavior using Trojan circuits in the original design. Traditional testing methods cannot detect these stealthy Trojans because the triggering scenario, which activates it, is unknown. Recently, approaches based on side-channel analysis have shown promising results in detecting Troja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 7 publications
0
42
0
Order By: Relevance
“…Prior Work: Detection of backdoors inserted by malicious foundries [12,16,17,24,40,53,69] TrustNET and DataWatch detects backdoors inserted by malicious chip designers (no prior solution)…”
Section: Tapeout and Fabrication Deploymentmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior Work: Detection of backdoors inserted by malicious foundries [12,16,17,24,40,53,69] TrustNET and DataWatch detects backdoors inserted by malicious chip designers (no prior solution)…”
Section: Tapeout and Fabrication Deploymentmentioning
confidence: 99%
“…In Section IV we describe our solution. Section V presents Incidents: [10] Attacks: [35] Solutions: This work Solutions: [12,16,17,24,40,53,69] No known attack/solutions Solutions: Trusted Processor Modules Device authentication mechanisms.…”
Section: Tapeout and Fabrication Deploymentmentioning
confidence: 99%
See 1 more Smart Citation
“…Banga et al [4,3] propose a region-based testing that first identifies the problematic regions based on power signatures and then performs more tests on the region. The underlying mathematical and logical circuit structure or the process variations are not considered.…”
Section: Related Workmentioning
confidence: 99%
“…Comprehensive reviews can be found in [2] and [3]. Several authors used the power supply transient current signal for Trojan detection [4]- [7]. Using the timing signal signature by testing multiple path signatures was suggested [8].…”
Section: Introductionmentioning
confidence: 99%